Medical Skills in a Clinical Presentation-Based Curriculum: Approach to the Patient With Diarrhea - Gordon Woods (Association of American Medical Colleges, 2015)
Abstract Introduction This module will guide clinical faculty as they organize and present a learning session for preclerkship medical students on the clinical work-up of a patient with diarrhea. During the session, students individually (or in pairs) work through the interview and perform the examination of a standardized patient presenting with diarrhea. After this encounter, students write a subjective, objective, assessment, and plan (SOAP) note, receive feedback from the standardized patient (and from their peer observer, if present) and debrief in a group discussion with a faculty member. Methods Provided materials include a readiness assurance quiz, preparatory exam room guide and video, summary outline for use during the standardized patient encounter, a checklist to guide peer observer feedback, and a standardized patient case blueprint. These materials would be of interest to preclerkship clinical skills instructors who would like to teach a presentation-based, focused history and physical exam to their trainees. Methods These materials were originally developed for the Medical Skills Course at the Texas Tech University Paul L. Foster School of Medicine (PLFSOM) in El Paso, Texas. Over the 5 years that we have used this case at PLFSOM, our first-year students have included the diagnosis of Crohn's disease in their top three diagnoses about 80% of the time. Discussion Our conclusion is that the majority of pre-clerkship medical students are indeed able to perform a structured interview and exam of this complexity, use their findings to successfully navigate the scheme diagram, and assign a high likelihood to the correct disease mechanism and diagnosis.